Evaluation of the Stock Quote – Stochastic Approach, Market Efficiency and Technical Analysis - BrÄƒtian, Vasile; Opreana, Claudiu; Bucur, Amelia (International Journal of Economics and Financial Issues, 2017)
The paper presents, theoretically and practically, the evaluation of the stock quote using the stochastic technique, market efficiency and the technical analysis, and the object of the study is the stock quote of Electrica SA, listed on the Bucharest Stock Exchange. One of the current paradigms, in which the stock quote is evaluated, considers this to be a random variable of continuous type. Our developments are subject to this paradigm. We also consider the technical analysis of the stock quote used in the study, complementary to the stochastic calculation. Prior to the technical analysis is carried out a test of the weak-form market efficiency, required to justify such an approach. Keywords: stochastic calculation; market efficiency; technical analysis JEL Classifications: C02, C13, G14, G17